Lack of Contentment as The Root of Corruption (1Tim 6:3-10): Nigerian Experience - Ezeogamba, Anthony Ezeogamba (International Journal of Culture and Religious Studies, 2023)
Contentment is a life of happiness and satisfaction with what one has. It is, in Igbo parlance, against "Ita abacha na aro akpu anya".[1] This is one of the greatest virtues that the majority of people lack. Nigeria under Gen. Obasanjo and Alhaji Atiku Abubakar according to Deputy National Publicity Secretary of APC, Mr. Yekini Nabena spent $16 billion on the power sector during their tenor as president and vice yet there is nothing to show for it.[2] One wonders whether the money was shared or what? The question was asked because those managing the affairs of the country at the point were financially well-to-do. The majority feel that the money was embezzled. Lack of contentment and embezzlement of the fund are what make some countries today to be failed states. It is what makes people get trapped into all sorts of foolish and harmful ambitions which plunge people into ruin and destruction (1 Tim 6:9). Hence, Paul says, "Love of money is the root of all evils" (1 Tim: 10). Nigeria is a country highly blessed with rich natural recourses like petroleum, coal, Iron ore, Limestone, Uranium, etc, yet Nigeria has practically nothing to show for them, instead, backwardness has become her lot. The question one has to ask is, how contented are Nigerians and their leaders? This paper aims at showing that if the political leaders, as well as citizens of Nigeria, are contented with what they have, Nigeria would have been the envy of the whole world. The researcher employed Historical-Critical (HC) and Textual Critical (TC) Methods to interpret 1 Tim. 6:3-10. HC Method is used because we are handling an ancient text - 1 Tim. 6:3-10. This will enable us to understand the world behind the text. TC Method was also employed for us to arrive at the original words of Paul in 1 Tim. 6:3-10 so as to avoid misinterpreting his thought. These methods were also used to analyze the generated data. The writer discovered that the greatest problem we have in Nigeria is that the majority of her politicians and citizens are greedy and incontinent hence, lack of development is the other of the day. The writer, as a matter of policy, recommends among other things that before anyone can be elected to be president, that person must convincingly show that he is contented with what he has. Hence, contentment is the answer. Significantly, this paper shall be relevant to both Nigerians and indeed every institution or nation that wants to develop.